Spectrophotometric determination of Atorvastatin Calcium in pharmaceutical by charge transfer complexation - Antakli, Saad; Nejem, Leon; Kullah, Ahmad (Journal of natural sciences, life and applied sciences, 2022)
Rapid useful and easy spectrophotometric method for the quantitative analysis of (Atorvastatin calcium) (ATV) in raw material and tablets pharmaceutical formulation has been described. This method is based on the formation of yellow ion-pair complex between Atorvastatin calcium and Bromocresol purple (BCP) in Dichloromethane medium. Different parameters affecting the reaction such as: effect of solvents, stability, reagent concentration, correlation ratio, etc. were optimized. The absorbance of the formed compound was measured by visible spectrum at absorption maximum 405 nm. The range of linearity was 3.02 – 42.33 µg/mL, , regression analysis had a good correlation coefficient R2 = 0.9994. The limit of detection (LOD) and limit of quantification (LOQ) were to be 0.463 µg/mL and 1.403 µg/mL respectively. The (average percent recovery) was found to be (99.26 – 99.85) % for (Atorvastatin Calcium). This study was applied on Syrian pharmaceutical products: (Atoraz 20 mg & Atoraz 40 mg). The method was successfully applied for the determination of Atorvastatin calcium in tablets pharmaceutical formulation. The proposed method is simple, direct, sensitive doesn’t require any )extraction( process. Thus, the method could be ready to apply in routine analysis and quality control.